(untitled) (Research, Society and Development, 2022)
From December 2019, a new pandemic ravages the world. The agent responsible for the new disease is the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Relentlessly, a race against time has begun to identify and decode the coronavirus 2019 (COVID-19) genome, in order to improve its diagnosis. Because it is a health problem, the clinical analysis laboratory has become a key player in the diagnosis because it is present in most Brazilian cities. Therefore, the aim of this literature review was to show which types of diagnostic tests can be performed by the clinical analysis laboratory. The methodology used was a bibliographic research from secondary sources, using the ScienceDirect and Pubmed database. The survey showed that the diagnosis of COVID-19 can be based on: biomarkers correlated to the virus itself (genetic material), the gold standard test being the real-time reverse transcription polymerase polymerase chain reaction (RT-PCR) assay; in molecules from the immune response against viral antigens (antibody production) by serological tests (enzyme immunoassays, chemiluminescent microparticle, fluorescence and lateral flow), and in changes in the concentration of biomarkers of organs affected by the virus (inflammatory markers, markers of kidney and liver function, etc.). Thus, in view of the increasing number of cases and the emergence of new variants, it is of utmost importance to spread knowledge and emphasize the importance of clinical laboratories in the daily life of communities, in the face of a pandemic.